PEDAGOGICAL DIAGNOSIS AS A MEANS OF DEVELOPMENT CREATIVE ABILITIES OF FUTURE TEACHERS - L.O. Savchenko (Academy of Cognitive and Natural Sciences, 2007)
In article problems of pedagogical diagnostics, and influence on development of creative abilities of students are considered during training in the higher school.